The Role of Autophagy in iNKT Cell Development - Yang, Guan; Driver, John P.; Van Kaer, Luc (Frontiers in Immunology, 2018)
CD1d-restricted invariant natural killer T (iNKT) cells are innate-like T cells that express an invariant T cell receptor -chain and recognize lipid antigens. They can rapidly respond to agonist activation and stimulate an extensive array of immune responses. Thymic development and function of iNKT cells are regulated by many different cellular processes, including autophagy, a self-degradation mechanism. In this mini review, we discuss the current understanding of how autophagy regulates iNKT cell development, effector lineage differentiation, and function. Importantly, we propose that iNKT cell development is tightly controlled by metabolic reprogramming.